The Narrative of Hope in “Suara Muhammadiyah, 02/2025 Edition”: A Critical Discourse Analysis Using Van Dijk’s Approach - Ulfa Afifa Widyastuti; Hanik Mahliatussikah; Khaled Ahmed Mahmoud Ahmed; Aan Khosihan (UIN Raden Mas Said Surakarta, Indonesia, 2025)
Following the 2024 General Election, Indonesia has faced a challenging situation marked by social polarization and intense political tensions that threaten national unity. In such conditions, Islamic da’wah cannot rely solely on conveying religious teachings in a normative manner. It is required to serve as a calming force capable of embracing various groups and re-strengthening social bonds within a divided society. This study aims to examine how da’wah communication strategies are employed by Muhammadiyah in constructing a hopeful narrative in the Main Feature Section of Suara Muhammadiyah magazine, 02/2025 edition. Published shortly after the 2024 election, this edition reflects Muhammadiyah’s stance on various sociopolitical issues at the national level. The study is relevant as the da'wah presented not only conveys religious messages but also acts as a form of symbolic intervention in the national public sphere. The study employs a descriptive qualitative approach using documentation and literature review techniques. The primary data source is the Main Feature Section of Suara Muhammadiyah 02/2025 edition, supported by secondary data from scholarly references. The analysis applies Teun A. Van Dijk’s Critical Discourse Analysis (CDA) framework, which includes three dimensions: textual structure, social cognition, and social context. The findings reveal that the da'wah messages are crafted using optimistic diction, supported by factual data, and reinforced with quotations from national figures. This strategy constructs a credible image while also fostering a sense of unity within society. From an academic perspective, this study contributes to the development of religious discourse studies. Meanwhile, on a practical level, the findings can be utilized in text-based Indonesian language learning, particularly to enhance students’ critical reading and argumentative writing skills. Setelah Pemilu 2024, bangsa Indonesia menghadapi situasi yang tidak mudah—terjadi polarisasi sosial dan ketegangan politik yang cukup tajam, yang berpotensi meretakkan persatuan. Dalam kondisi seperti ini, dakwah Islam tidak cukup hanya menyampaikan ajaran-ajaran keagamaan secara normatif. Ia dituntut untuk tampil sebagai kekuatan yang menenangkan, yang mampu merangkul berbagai kelompok, serta menguatkan kembali ikatan sosial di tengah masyarakat yang sedang terbelah. Penelitian ini bertujuan untuk mengkaji bagaimana strategi komunikasi dakwah yang diterapkan oleh Muhammadiyah dalam menyusun narasi penuh harapan pada rubrik Sajian Utama majalah Suara Muhammadiyah edisi 02/2025. Edisi ini terbit setelah Pemilu 2024 dan menjadi cerminan bagaimana Muhammadiyah mengambil sikap terhadap berbagai isu sosial-politik yang berkembang di tingkat nasional. Kajian ini menjadi relevan karena dakwah yang disampaikan tidak hanya sebatas menyuarakan ajaran agama, tetapi juga memainkan peran penting sebagai bentuk intervensi simbolik dalam ruang publik kebangsaan. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik studi dokumentasi dan telaah pustaka. Sumber data utama adalah rubrik 'Sajian Utama' edisi 02/2025 majalah Suara Muhammadiyah, sementara data sekunder diperoleh dari berbagai referensi ilmiah. Analisis dilakukan dengan pendekatan Analisis Wacana Kritis model Teun A. van Dijk yang mencakup tiga dimensi: struktur teks, kognisi sosial, dan konteks sosial.. Hasil penelitian memperlihatkan bahwa pesan dakwah dirangkai menggunakan pilihan kata yang optimis, dilengkapi data faktual, dan diperkuat dengan kutipan dari tokoh-tokoh nasional. Strategi ini membangun citra yang kredibel sekaligus menumbuhkan rasa kebersamaan di tengah masyarakat. Secara akademik, kajian ini memberi kontribusi bagi pengembangan studi wacana keagamaan. Sementara secara praktis, temuan ini dapat dimanfaatkan dalam pembelajaran Bahasa Indonesia berbasis teks, khususnya untuk melatih kemampuan membaca kritis dan menulis argumentatif.